Recognition and management of delirium among doctors, nurses, physiotherapists, and psychologists: an Italian survey. (December 2014) - Bellelli, G.; Morandi, A.; Zanetti, E.; Bozzini, M.; Lucchi, E.; Terrasi, M.; Trabucchi, M.; Koopmans, Raymond; Rosness, Tor
ABSTRACT Background: There are no studies that have identified the ability to recognize and manage delirium among Italian health providers caring for patients at risk. Therefore, the Italian Association of Psychogeriatrics (AIP) conducted a multicenter survey among doctors, nurses, psychologists and physiotherapists to assess their competence regarding the theme of delirium and its management in the everyday clinical practice. Methods: The survey period was 1st June 2013 to 30th November 2013. The invitation to participate was sent via email, with publication on the AIP website. The survey included 14 questions and two case vignettes. Results: A total of 648/1, 500 responses were collected. Most responders were doctors (n = 322/800), followed by nurses (n = 225/500), psychologists (n = 51/100), and physiotherapists (n = 30/100). Generally, doctors and psychologists correctly defined delirium, while nurses and physiotherapists did not. The most frequently used diagnostic tools were the Confusion Assessment Method (CAM) and the Diagnostic and Statistical Manual of Mental Disorders-IV. Delirium intensity was rarely assessed. Hypoactive delirium was generally managed with non-pharmacological approaches, while hyperactive delirium with a combination of non-pharmacological and pharmacological approaches. However, possible causes of delirium were under-assessed by half of doctors and by the majority of other professionals. Nurses, psychologists and physiotherapists did not answer the case vignettes, while doctors identified the correct answer in most cases. Conclusions: This is the first Italian survey among health providers caring for patients at risk of delirium. This is also the first survey including doctors, nurses, psychologists and physiotherapists. The results emphasize the importance of training to improve knowledge of this relevant unmet medical need.